Errors, Representations, and Instructional Coherence in a Secondary Mathematics Textbook: Evidence from the Grade 10 Curriculum in the Kurdistan Region of Iraq - Shwan Alshatri; Savyia Farouq (Universitas Papua, 2026)
Mathematics textbooks are central to classroom instruction and play a crucial role in supporting students’ conceptual understanding of mathematical ideas. Because textbooks often serve as the primary instructional resource, errors in their content may contribute to misconceptions, impede learning, and negatively affect students’ mathematical reasoning and problem-solving abilities. This study aimed to identify and analyze errors in the Grade 10 mathematics textbook used in secondary schools in the Kurdistan Region of Iraq during the 2015–2025 curriculum implementation period. A qualitative document analysis approach was employed through a systematic examination of textbook chapters, lessons, worked examples, exercises, graphical representations, and explanatory sections. The identified errors were classified into four categories: incorrectly solved examples, instructional and conceptual deficiencies, printing and graphical errors, and translation- or language-related errors. The analysis revealed eleven errors, including ten major errors and one minor error. Several of these errors were found to have the potential to adversely influence students’ conceptual understanding and mathematical performance. The findings highlight the importance of rigorous textbook evaluation and quality assurance procedures to ensure the accuracy, clarity, and pedagogical effectiveness of mathematics instructional materials in secondary education.